Targeting cardiac sympatho-vagal imbalance using gene transfer of nitric oxide synthase. - Danson, E; Li, D; Wang, L; Dawson, T; Paterson, D (2009)
Heightened sympathetic excitation and diminished parasympathetic suppression of heart rate, cardiac contractility and vascular tone are all associated with cardiovascular diseases such as hypertension and ischemic heart disease. This phenotype often exists before these disease states have been established and is a strong correlate of mortality in the population. However, the causal role of the autonomic phenotype in the development and maintenance of hypertension and myocardial ischemia remains a subject of debate, as are the mechanisms responsible for regulating sympathovagal balance. Emerging evidence suggests oxidative stress and reactive oxygen species (such as nitric oxide (NO) and superoxide) play important roles in the modulation of autonomic balance, but so far the most important sites of action of these ubiquitous signaling molecules are unclear. In many cases, these mediators have opposing effects in separate tissues rendering conventional pharmacological approaches non-efficacious. Novel techniques have recently been used to augment these signaling pathways experimentally in a targeted fashion to central autonomic nuclei, cardiac neurons, and myocytes using gene transfer of NO synthase. This review article discusses these recent advances in the understanding of the roles of NO and its oxidative metabolites on autonomic imbalance in models of cardiovascular disease.